A pragmatic methodology for studying international practices. (October 2021) - S Sundaram, Sasikumar; Thakur, Vineet
Practice turn marks an important advancement in International Relations theorizing. In challenging abstract meta-theoretical debates, practice theorizing in International Relations aims to get close to the lifeworld(s) of the actual practitioners of politics. Scholars from different positions such as constructivism, critical theory, and post-structuralism have critically interrogated the analytical framework of practices in international politics. Building upon these works, we are concerned with a question of how to examine the context of international practices that unfolds in multiple ways in practitioners' performances. Our central thesis is that a distinct pragmatic methodology offers an opportunity to keep with the practice turn and avoid the problematic foundational moves of mainstream practice theorizing. This involves foregrounding three interrelated processes in examining practices: the role of exceptions in the normal stream of performances, normative uptake of the analysts, and the semantic field that actors navigate in political performances. We argue that this methodology is predicated on its usefulness to interpret practices through reflective social-science inquiry.